THE HISTORY AND DYNAMICS OF TAFSIR IN THE TABI'IN ERA - Marwati, Andi; Hamzah, Idil (Ma'had Aly As'adiyah Sengkang, 2024)
The development of Quranic exegesis during the Tabi'in era, the second generation in Islam after the Companions of Prophet Muhammad, saw continued efforts within the Muslim community to understand and interpret the messages of the Quran to guide life and religious practices. When we revisit the discussed developments in exegesis, it becomes evident that each historical period has its unique characteristics. This research aims to explore the history of exegesis based on the Tabi'in period. The research method employed is a library research approach, gathering necessary information from various reference sources such as books, records, and research articles. The findings reveal that during the Tabi'in era, the activity of Quranic exegesis continued to evolve, giving rise to various schools, methods, and styles of interpretation. In the Tabi'in era, the development of exegesis was marked by the emergence of interpretive schools in Mecca, Medina, and Iraq. Exegesis development persisted with diversity in sources, styles, and methods of interpretation. This can be observed in the context of Tabi'in exegesis, where the primary sources still retained the interpretive methods used by the Companions, yet the Tabi'in began to engage in independent interpretation (ijtihad) and introduced new ways of thinking into their interpretations.